2017
DOI: 10.20944/preprints201703.0059.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fluid Flow and Mixing Induced by AC Continuous Electrowetting of Liquid Metal Droplet

Abstract: Abstract:In this work, we proposed a novel design of microfluidic mixer utilizing the amplified Marangoni chaotic advection induced by AC continuous electrowetting of a metal droplet situated in electrolyte solution, due to the linear and quadratic voltage-dependence of flow velocity at small or large voltages, respectively. Unlike previous researchers exploiting the unidirectional surface stress with DC bias at droplet/medium interface for pumping of electrolyte where the resulting flow rate is linearly propo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Under the Debye–Huckel limit, the electrostatic potential field in the bulk fluid and dielectric membrane are both governed by the Laplace equation with zero volumetric free charge density [ 55 , 56 , 57 , 58 , 59 ]: …”
Section: Methodsmentioning
confidence: 99%
“…Under the Debye–Huckel limit, the electrostatic potential field in the bulk fluid and dielectric membrane are both governed by the Laplace equation with zero volumetric free charge density [ 55 , 56 , 57 , 58 , 59 ]: …”
Section: Methodsmentioning
confidence: 99%
“…Yazdanshenas et al [ 24 ] developed a microfluidic Kelvin water dropper that can generate high-voltage electricity through water dripping and also used their device to replace the high-voltage power supply in electrowetting. Hu et al [ 25 ] demonstrated a microfluidic mixer design that utilizes amplified Marangoni chaotic advection induced by alternating current electrowetting of a metal droplet. Ahmed and Kim [ 26 ] presented a numerical parametric study of electroosmotic micro-mixers with heterogeneously charged surface patches on channel walls.…”
Section: Other Electric-field-mediated Phenomena (Seven Papers)mentioning
confidence: 99%
“…One of the most popular applications of LM droplet control is to use its high electrical and thermal conductivity in microfluidics as a micromechanical switch inside microchannels for thermal or electrical conduction [ 18 , 19 , 20 ]. Basic microfluidics components, such as micropumps [ 21 ] and mixers [ 22 ], are achieved by electrowetting (EW) controlled liquid metal droplets as well. Furthermore, Wu et al [ 23 ] have recently developed a wheelchair mobile robot with electrical movement control of LM droplets, thereby largely expanding its application scope.…”
Section: Introductionmentioning
confidence: 99%